2023
DOI: 10.1007/s11064-023-03861-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin Attenuates Exacerbation of Neuropathic Pain, Blood-spinal Cord Barrier Breakdown and Cord Pathology Following Chronic Intoxication of Engineered Ag, Cu or Al (50–60 nm) Nanoparticles

Abstract: Neuropathic pain is associated with abnormal sensations and/or pain induced by non-painful stimuli, i.e., allodynia causing burning or cold sensation, pinching of pins and needles like feeling, numbness, aching or itching. However, no suitable therapy exists to treat these pain syndromes. Our laboratory explored novel potential therapeutic strategies using a suitable composition of neurotrophic factors and active peptide fragments-Cerebrolysin (Ever Neuro Pharma, Austria) in alleviating neuropathic pain induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Another study also reported that after chronic intoxication of engineered silver, copper, or aluminum (50-60 nm) nanoparticles, CBL led to a decrease in the exacerbation of neuropathic pain, spinal cord pathology, and blood-spinal cord barrier breakdown. 30 Menon et al 31 examined the effect of intravenous iron oxide magnetic nanoparticles (10 nm in diameter and 0.25 or 0.50 mg/mL in 100 μL) in SCI animals and the therapeutic efficacy of CBL. The results showed that CBL therapy significantly reduces iron oxide magnetic nanoparticleinduced aggravation of SCI-induced cord pathology and improves neuroprotection.…”
Section: Cerebrolysin In Spinal Cord Injurymentioning
confidence: 99%
“…Another study also reported that after chronic intoxication of engineered silver, copper, or aluminum (50-60 nm) nanoparticles, CBL led to a decrease in the exacerbation of neuropathic pain, spinal cord pathology, and blood-spinal cord barrier breakdown. 30 Menon et al 31 examined the effect of intravenous iron oxide magnetic nanoparticles (10 nm in diameter and 0.25 or 0.50 mg/mL in 100 μL) in SCI animals and the therapeutic efficacy of CBL. The results showed that CBL therapy significantly reduces iron oxide magnetic nanoparticleinduced aggravation of SCI-induced cord pathology and improves neuroprotection.…”
Section: Cerebrolysin In Spinal Cord Injurymentioning
confidence: 99%